Personalized energy monitoring and possibilities of its use in perioperative management of patients with hiatal hernia - V.I. Cherniy; A.I. Denysenko (Медицина неотложных состояний, 2022)
Background. The study of perioperative changes in metabolism in patients undergoing laparoscopic surgeries for hiatal hernia is relevant. The purpose was to study the use of personalized energy monitoring of patients with hiatal hernia and to evaluate its possibilities in perioperative management. Materials and methods. The study was prospective, non-randomized and included 132 patients aged 32–77 years (64 men and 68 women), who underwent laparoscopic surgeries for hiatal hernia. Preoperative risk was ASA II–III. General anesthesia was performed using the inhaled anesthetic sevoflurane and the narcotic analgesic fentanyl in conditions of low-flow artificial lung ventilation. Operational monitoring was supplemented by indirect calorimetry. In group I (n = 66), the metabolic rate (MR) and basal metabolic rate (BMR) were determined against the background of standard intensive care. In group II (n = 66), target metabolic rate (TMR) and the metabolic disorders (MD = × 100 %) were evaluated additionally, and intensive care was supplemented by additional infusion therapy and glucocorticoids, taking into account MR, TMR and MD. Results. Baseline MR indicators were without violations and significantly exceeded BMR (in group I — by 30 %, in group II — by 29 %). At the stage of reverse Trendelenburg position, pneumoperitoneum and the beginning of the operation, the patients had significant violations of MR with a decrease to BMR. In group I, there was a slow restoration of MR, which at the time of awakening was 8.2 % lower than the baseline (p < 0.05). In patients of group II, against the background of intensified infusion therapy and administration of glucocorticoids, MR restoration was more intense, with a decrease in MD to a safe level (5.4 ± 2.7 %), and in MR to the baseline (p < 0.05). Patients of group II woke up faster and were transferred to the ward, and nausea and vomiting were 2.2 times less frequent in them than in group I (p < 0.05). According to the visual analogue scale, postoperative pain 6 and 12 hours after waking up in group II was lower than in group I by 29 and 35.5 % (p < 0.05), respectively. Conclusions. Personalized perioperative energy monitoring makes it safer to perform surgical interventions in patients with hiatal hernia. Additional evaluation of the target metabolic rate and the metabolic disorders allows more effective perform perioperative intensive care.